О ВЛИЯНИИ ЭЛИМИНАЦИОННЫХ ДИЕТ НА ФИЗИЧЕСКОЕ РАЗВИТИЕ ДЕТЕЙ, СТРАДАЮЩИХ АЛЛЕРГИЧЕСКИМИ ЗАБОЛЕВАНИЯМИ - Васильев, Юрий Валерианович; Вавилова, Наталия Алексеевна; Яралиева, Шамсият Кехлеровна (FORCIPE, 2022)